Antisolvent-induced encapsulation for extraction/preconcentration of silver nanoparticles - Ali Daneshfar; Reza Sahrai (شیمی کاربردی روز, 2012)
In this research work a simple and very fast antisolvent-induced encapsulation procedure was developed and applied for extraction and preconcentration of silver nanoparticles from diluted aqueous solutions. Organic solvent (1.0 ml) was added to a solution of silver nanoparticles capped with starch (2.0 ml) for formation of a homogeneous solution. To the mixture solution, suitable amount of ammonium sulfate (0.30 g) was added and the solution was vigorous shaken until the salt was completely dissolved. Then 1.0 ml of organic antisolvent was added, after which it was separated into two clear phases by centrifugation at 3000 rpm for 5 min. The influences of effective parameters such as salt (type and amount), organic solvent, and its volume were studied and optimized.